Multiple group membership supports resilience and growth in response to violence and abuse. (14th September 2021) - Haslam, Catherine; Latilla, Tatiana; Muldoon, Orla T.; Cruwys, Tegan; Kearns, Michelle
Abstract: This paper examines the role that social group processes, and multiple group membership in particular, play in supporting resilience and post‐traumatic growth following the experience of violence and abuse. Drawing on social identity theorizing, we develop and test a model that (a) predicts an association between multiple group membership and positive outcomes of resilience and post‐traumatic growth, and (b) explores mechanisms, of personal control and identification with anti‐violence activists, through which group membership might exert this effect. This model was tested using data from a sample of predominantly White South African adults recruited through numerous sources including a non‐government organisation that supports victims of violence and abuse ( N = 112). Results showed that multiple group membership was positively related to post‐traumatic growth and provided a basis for enhanced personal control and identification with activists. Personal control also mediated the relationship between multiple group membership and resilience. We discuss the implications for theory and practice and suggest there is value in working with social group memberships following trauma to support recovery.